Investigations of Ni-SDC carbonate (Ni-SDCC) as composite anode for low temperature solid oxide fuel cells - Ng, Kei Hoa (2018)
Systematic research regarding NiO-SDC carbonate (NiO-SDCC) as composite anode is limited despite great chemical compatibility and cell performance achieved with other low temperature solid oxide fuel cell (LTSOFC) components. This study focuses to investigate the correlation of powder composition and calcination temperature on the chemical compatibility, morphologies, thermal and electrochemical performance of NiO-SDCC composite anode. NiO-SDCC composite powders with the weight ratios of 50:50 (NC55), 60:40 (NC64), and 70:30 (NC73) were achieved using high-energy ball-milling. All powders were calcined at 600–800 °C, pelletized and sintered at 600 °C. Characterisation include the crystalline phases, thermogravimetry, thermal expansion coefficient (TEC), hardness and morphologies were conducted. Electrochemical impedance spectroscopy (EIS) was conducted under in-situ reduction process. The powder and pellet morphologies, thermal expansion, and hardness were mostly affected by the calcination temperature as compared to powder composition. NC55 was selected for anode reduction process in hydrogen due for the least TEC values as compared to NC64 and NC73. The Ni-SDCC exhibited porosity of 36-40% after reduction process. The lowest area specific resistance of 5.3 Ωcm2 was achieved with sample calcined at 800 ℃. In this study, unexpected mechanical failure has been observed after EIS measurements. Therefore, chemical reactions and anode failure mechanisms were successfully proposed in this study. This mechanism is a new finding that has not been reported in previous studies and must be given appropriate attention. In conclusion, this study significantly contributes to the development of Ni-SDCC as LTSOFC composite anode. Further enhancement on this material is required on improved durability for LTSOFC application.